Reconstructing Two Decades of Inequality in the Sahel Region - Gianni Betti; Federico Crescenzi; Hai-Anh Dang; Vasco Molini; Lorenzo Mori (Global Labor Organization (GLO), 2025)
Measuring inequality in West Africa is a challenging task that is constrained by the limited availability and irregular collection of household consumption data. To address this challenge, we reconstructed the evolution of inequality in the Sahel region using an innovative framework that combines Survey-to-Survey Imputation Techniques (SSITs) with Generalized Additive Models for Location, Scale and Shape (GAMLSS), based on labour force surveys conducted in eight countries between 2003 and 2021. The findings highlight pronounced regional disparities, persistent levels of inequality, and a clear association between inequality patterns and episodes of conflict or political instability. Our contribution is twofold: methodologically, we introduce a flexible SSIT-GAMLSS model that incorporates two levels of random effects; substantively, we provide new evidence of inequality trends in francophone West Africa, a region largely underrepresented in empirical research.
Keywords: C15; I32; O15; 330; inequality; imputation; labour force surveys; West Africa